Teaching students to collaborate – insights from interprofessional education development - Mira Mette; Jutta Hinrichs (Zeitschrift für Hochschulentwicklung, 2023)
Since (interdisciplinary) collaboration skills are considered essential to thrive in an unpredictable and uncertain future, higher education is demanded to train students to develop collaboration fluency. However, there are no clear guidelines for effective collaboration skills trainings. Thus, different ideas and reflections on theoretically underpinned pedagogical designs, assessment approaches and the alternating role of teachers (experts vs facilitators) are given and – where possible – illustrated with our experience in developing and implementing interprofessional education. Implications for teachers and higher education institutions are derived.